Assessing the Six-Factor Model of Organizational Justice in the Context of Workplace Mediation. (September 2020) - Coggburn, Jerrell D.; Daley, Dennis M.; Jameson, Jessica Katz; Berry-James, RaJade M.
Applying the six-factor model of organizational justice, this study examines the relationship between disputants' (i.e., grievants and respondents) perceptions of organizational justice and satisfaction with workplace mediation. Using secondary data, collected postmediation from participants in the (former) North Carolina Department of Correction's (DOC) mediation process, the findings show that perceptions of organizational justice and mediation satisfaction are high for both grievants and, especially, respondents. Logistic regression results find statistically significant relationships between mediation satisfaction and three factors of organizational justice—distributive justice, procedural justice–process, and disputant–disputant interpersonal justice—as well as unexpected results for procedural justice–mediator and disputant–mediator interpersonal justice.